Persepsi Guru PAI SMP Tentang Toleransi pada Mata Pelajaran PAI di Kota Padang - Dewi Sarina; Rini Rahman (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
The purpose of this paper is to find out how PAI teachers perceive tolerance in PAI subjects. The qualitative method with a phenomenological approach is the method used in this study. Informants in this study focused on PAI teachers in class VIII of State Junior High Schools in Padang City who were selected using a purposive sampling technique. Researchers determined as many as nine informants or 12 percent of the total number of PAI teachers at State Junior High Schools in Padang City. Three data collection techniques used are observation, interviews, and documentation. Overall, this study shows that PAI teachers in class VIII at the State Junior High School level in Padang City already know the concept of tolerance which is in line with the notion of religious moderation. Then the results of this study also show that in addition to knowing the concept of tolerance, PAI teachers also implement it in PAI learning in schools. Such as through mutual respect advice at the beginning of learning, optimizing learning materials related to tolerance, namely material on halal food and drinks, and praying sunnah in the congregation.